2022
DOI: 10.47582/jompac.1080105
|View full text |Cite
|
Sign up to set email alerts
|

Tip 2 diyabet hastalarında dolaşımdaki B-tipi natriüretik peptidin osteoporoz ile ilişkisi

Abstract: Objective: The aim of this study was to evaluate the relationship of circulating B-type natriuretic peptide (BNP) with osteoporosis in type 2 diabetes mellitus (T2DM) patients. Material and Method: 95 patients with T2DM were included in the study. Patients with circulating BNP levels in their patient file systems and whose BMD were measured within 15 days were included in the study. The patients were divided into three groups according to their BMD scores as normal, osteopenia and osteoporosis. The relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
(13 reference statements)
0
1
0
Order By: Relevance
“…In studies conducted in T2DM patients, a negative correlation was found between circulating BNP and BMD. [ 26 ] In our study, we found that increased serum NT-pro-BNP levels were associated with decreased lumbar T-scores, and serum levels of NT-pro-BNP were an important and independent predictor of lumbar BMD in PD patients.…”
Section: Discussionmentioning
confidence: 66%
“…In studies conducted in T2DM patients, a negative correlation was found between circulating BNP and BMD. [ 26 ] In our study, we found that increased serum NT-pro-BNP levels were associated with decreased lumbar T-scores, and serum levels of NT-pro-BNP were an important and independent predictor of lumbar BMD in PD patients.…”
Section: Discussionmentioning
confidence: 66%